THE RESULT OF FLOW MEDIATED DILATION TEST IS NOT A DICHOTOMOUS – THE INITIAL STUDY. (June 2018) - Stanczyk, A.; Krzesinski, P.; Piotrowicz, K.; Banak, M.; Chcialowski, A.; Rozbicki, P.; Dabrowiecki, P.; Badyda, A.; Gielerak, G.
Abstract : Objective: The flow mediated dilation test (FMD) is a standard of examination of an endothelial activity. Positive result is defined as an augmentation of diameter of brachial artery in reaction to hyperaemia estimated for more than 7% of initial value. According to the different methodologies the measurement is performed in a one defined time-point from 2. to 5. minute after the cuff deflation. The aim of the study was to analyze a multipoint time sequential measurements of brachial artery diameter during FMD test. Design and method: In a 70 volunteers (33% men, 50+/−14 y.o.) without previous cardiovascular history, FMD test was performed. Cuff of a manometer was placed in a medium of a forearm. Cuff was inflated to a value of 50mmHg higher than systolic blood pressure for a 5 minutes. Brachial artery diameter was measured in a standard acquisition's point before the cuff inflation, just after the deflation (0′) and in every one minute during 5 consecutive minutes (1′ – 5′) period. According to the percentage changes of a brachial artery's diameter the models of the reaction were estimated. Results: According to a differences in a direction of changes and time dependent arterial reactivity a six models of FMD reaction was proposed (fig.1) Type 1. – "standard reaction" - the highest diameter observed in a 2. minute after deflation Type 2. – "early reaction" – the highest diameter observed just after deflation Type 3.– "late reaction" – the highest diameter observed between 3. and 5. minute after deflation Type 4. – "early constrictive reaction" the initial constrictive reaction observed before a dilation Type 5. – "constrictive reaction" – constriction of artery observed during the whole post-dilation period Type 6. – "lack of reactivity" lack or a relative changes (lower than 2% of a diameter) observed during the whole post-dilation period. Figure. No caption available. Conclusions: Multipoint time sequential measurements during FMD provides additive cognitive value to the standard FMD test. Clinical relevance of different types of vascular reaction needs a further evaluation.